A Review of Toxoplasmosis and Neosporosis in Water Buffalo (Bubalus bubalis) - de Barros, Luiz Daniel; Garcia, João Luis; Bresciani, Katia Denise Saraiva; Cardim, Sérgio Tosi; Storte, Victor Sesnik; Headley, Selwyn Arlington (Frontiers in Veterinary Science, 2020)
Toxoplasmosis and neosporosis are diseases with worldwide distribution and are associated with reproductive problems in livestock and are responsible for economic losses. This review presents an overview of the current knowledge relative to these diseases in water buffalo (Bubalus bubalis). In general, buffaloes are considered resistant to clinical toxoplasmosis, since there are studies only reporting serological evidence of natural infection in these animals. Studies have described age, poor hygienic status of the farm, and presence of cats as risk factors for the development of T. gondii infection in buffaloes. It must be highlighted that buffalo meat which does not receive adequate freezing treatment and could be a potential source for toxoplasmic human infection and the importance of raw buffalo milk in the transmission of toxoplasmosis to humans being. Neospora caninum is considered one of the major causes of abortion and responsible for huge economic losses in cattle. Vertical transmission is the main route to infect calves, and it is responsible for maintaining the parasite within a herd. In buffaloes, vertical transmission was also described; moreover, although there are indications that N. caninum may be associated with abortion in dairy buffaloes, the reproductive importance of neosporosis is apparently lower in buffaloes relative to cattle. Most studies have identified a higher time of exposition to N. caninum oocysts relative to age. The household system was also described as a risk factor for infection, possibly due to persistent contact between the home-raised buffaloes and canids. The fetal immune competence of buffaloes is similar to bovine and buffalo fetus are highly susceptible to infection during the first trimester of pregnancy, indicating that N. caninum may be an abortigenic agent in buffaloes. Alternatively, it is interesting to note there are evidences that the inflammatory response in pregnant buffaloes infected with N. caninum is mild enough to avoid abortion in most of the cases. It is proposed that the possible transmission of toxoplasmosis through unprocessed milk and buffalo meat may occur, which is important in terms of public health. Additionally, there is strong evidence to suggest that N. caninum may be associated with abortion in buffaloes.